„Kraj wolności” i „kraj niewoli” – brytyjska i francuska wizja wolności – XVII-XVIII wiek - Napierała, Piotr (My University, 2010)
Niniejsza praca dotyczy problematyki zarówno myśli politycznej i teorii ustroju jak i historii społecznej. Interesowała mnie wolność polityczna rozumiana jako zbiór idei dotyczących przestrzeni między rządzącymi a rządzonymi czy miedzy administracją a poddanymi/obywatelami. Wolność religijna czy kwestie związane z uciskiem jakichś mniejszości etnicznych czy wyznaniowych były dla mnie istotne jedynie wówczas, gdy były one ściśle powiązane z ogólną wizją wolności politycznej danego myśliciela czy stronnictwa. "Wolność", o jakiej mowa w tytule to przede wszystkim ta wolność, którą Isaiah Berlin określał mianem "negatywnej" ("wolność od"), postulującej uniezależnienie jednostki od państwa, i pozbawienie aparatu państwowego możliwości nadmiernej ingerencji w życie poddanych/obywateli.Pracę podzieliłem na sześć rozdziałów. W rozdziale pierwszym umieściłem niezbędny zarys historii myśli politycznej dotyczącej problemu wolności politycznej, jak i form ustrojowych, zarówno tych które miały być realizacją koncepcjo wolnościowych jak i tych, które krytykowano powołując się na wolność.W rozdziale drugim poddałem analizie proces kształtowania się angielskich wyobrażeń i idei związanych z problemem wolności. Zwróciłem w nim uwagę na takie problemy jak: - elżbietański mit historyczny; -post-normańska więź łączącą angielskich arystokratów, wypływającą z zasady "wasal mego wasala jest moim wasalem", -wigowski mit historyczny, a więc postrzeganie dworu królewskiego jako ośrodka dążącego do absolutyzmu.- długo utrzymująca się, wbrew obiegowym opiniom, wiara w skuteczność ekonomicznego merkantylizmu W rozdziale trzecim omówione zostały kwestie na pograniczu historii francuskiego ustroju absolutystycznego, tworzonego w teorii przez Bodina, Domata i Bossueta, a w praktyce przez Richelieugo i Colberta, a kwestią wolności poddanych Ludwików francuskich. Rozdział IV poświęciłem kwestiom związanym z wolnością w XVIII-wiecznej Wielkiej Brytanii. Podkreśliłem w nim angielskie przywiązanie do wolności prasy, której płomienne mowy poświęcali m.in. Hume i Defoe, przy jednoczesnym niedostatku tolerancji religijnej (w końcu sam Locke odmawiał jej katolikom). Uwagę moją przykuły zaskakująco małe różnice między Torysami i Wigami w kwestii konieczności zachowania "wolności negatywnej". Rozdział V zawiera rozważania nad zakresem swobody poddanych Ludwika XV i Ludwika XVI, a także takich kwestii jak neofeudalizm (min. Henri de Boulainvillersa); wypływający z francuskiego tradycyjnego sposobu rozumienia wolności w pewnym stopniu odpowiadającemu postulatom "wolności negatywnej" - arystokratycznemu marzeniu o niezależności od stolicy i o tym, że powinna się ona nie wtrącać do ich spraw. W rozdziale IV znaleźć można również omówienie koncepcji reform opartych na postulacie osiągnięcia możliwie daleko posuniętej wolności; od "angielskich" planów Voltaire'a i Vauvenarguesa po proto-socjalistyczne Rousseau i d'Holbacha i centralistyczne fizjokratów. Tak jak w rozdziałach tych świadkowie omawianych czasów będą wypowiadać się o swoim państwie i swojej tradycji politycznej, tak rozdział VI i ostatni poświęcony jest wyobrażeniom dotyczącym wolności; Anglików/Brytyjczyków o Francji i odwrotnie.

In my doctoral thesis: „Kraj wolności” i „kraj niewoli” - brytyjska i francuska wizja wolności – XVII i XVIII wieku (A ‘country of liberty’ and a ‘country of slavery’ – The British and French Concept of political Liberty in 17th and 18th Century) I attempted to compare the British and the French concepts of political freedom which were being developed in course of the 17th and 18th centuries. My idea was to examine if the popular vision of the early modern France as the ‘county of political slavery’ and – in the same time – of Britain as a mecca for every freedom-lover is really justified. In this case both political thought and ideas of various thinkers and informations about the reality of that era were of great interest of mine. My PhD Thesis is divided into six chapters. In the first chapter I attempted to present an abstract of the general history of possibile Liberty concepts. In the next chapter my aim was to discover why so many British (not only political) political authors of the 17th and 18th centuries are so much concerned about the problem of individual and public liberty. I have analysed the so-called „whiggish historical myth”, according to which the whole English (after 1707 – British) political history is perceived as a great struggle for freedom against various ‘oppressors’ such as: Roman Empire, the Papacy, Spain of Charles V and Philip II, France of Louis XIV, Louis XV, Robespierre and Napoleon Bonaparte. I dealt with the koncept of the so much praised English „monarchia mixta’ in which the aristocratic, the democratic and the monarchical elements of the government co-exist in a splendid harmony, whithout which, as it was believed, England would have fallen into a state of horrid tyranny and its people – into slavery. I tried to understand why the Britons living in the early modern era called the French: pope-ridden, wooden-shoed slaves. On the other hand I analised the first absolutist treatises written in England (Robert Filmer, Thomas Hobbes etc.) to observe the arguments used in them especially those concerning political liberty. The same I did in the third chapter with French treatises written by local adherents of ‘king’s divine rights’ (Domat, Bossuet, Le Bret etc.) and its relation to individual liberty. The ‘voice of nobility’ of both nations was also of great interest to me because diffrent historical experiences defined different koncept of liberty of the rich and powerful. In the post-norman Britain the nobility was accustomed to co-operate in the king’s government whereas in France they used to fight against him especially when he attempted to extend his political influence. The aristocratic version of political freedom is best represented by Sunderland’s and Boulainvilliers’ concepts developed independently on both sides of the Channel in the first half of the 18th century. In the fourth chapter I analysed the new ideas concerning freedom and political Liberty created by the Anglo-Scottish enlighenment. The koncept of the freedom of the press (Defoe, Hume), the individualisation of a subject, new vision of the just law and new thoughts on mutiny (Johnson, Burke) and slavery. The following chapter is devoted to the various concepts of French political thought in the 18th century, such as: the monarchical idea of Voltaire, the thèse nobiliaire of Montesquieu and Boulainvilliers, the plan of administrative decentralisation of d’Argenson, the ‘american’ vision of Diderot, Mercier and Condorcet, as well as the first clearly democratic and pre-ocialist ideology represented by Meslier, Rousseau an Morelly. The diversity of al. those thinkers used to thundestand by ‘liberty’ convinces me that there was no national ideas of liberty but merely a number of various ideas created by a number of political philosophers and this fact makes even today very hard to define what we perceive as ‘liberal thinking’. All the aforementioned ideas are confronted with facto stated by historians specialising in the 17th and 18th centuries. In sixth and the last chapter I have presented the evolution in French vision of the ‘English liberty’ and the other way round and how they looked like prom perspective of several 19yh and 20th century thinkers of various ideological background.
A ‘country of liberty’ and a ‘country of slavery’ – The British and French Concept of political Liberty in 17th and 18th Century
Wydział Historyczny: Instytut Historii
Keywords: Wigowski mit historyczny; Whig historical myth; Liberalizm; Liberalism; Myśl polityczna; Political thought; Nowożytność; New modern era; Elżbietanizm; Elisabethanism; Neofeudalizm; Neo-feudalism; Francja; France; Wielka Brytania; Great Britain; Locke; Voltaire